Estimation of Age @ Death by Counting Number of Osteons from the Sternal RIB (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Identification of an individual becomes essential in a dead body more than when he is alive. Identitybecomes a problem in a dead person when the body is decomposed, mutilated, in skeletal remains or in masscausality death. The foremost essential thing in medico legal cases, becomes identity of the dead , rather thanopinion about the cause of death, time since death or manner of death. The aim of this study was to arrive at theregression formula for assessing the age of the dead, based on the number of osteons in the sternal rib bone.Methods : The study involved 41 sternal ribs taken from 20 to 50 years old persons from the south Indianpopulation at Institute of Forensic Medicine Department Madras Medical College. After autopsy a portion of ribbone was removed from the shaft of the fourth sternal rib near their anterior ends. A slide from the bone sectionwas placed in the light microscope to study the number of osteons in full thickness of the compact bone of the rib.Result & Conclusion: In this study, age was plotted in the X– axis and the number of osteons were plotted in theY – axis. A correlation coefficient (r) is derived. It summarizes the significance in the relationship of two variables.This study illustrates the estimation of age at death by counting the number of osteons in the rib bone from the agegroup of 20 to 48 years. It was proved that the number of osteons increases with age.
Keywords: Identification,skeletal remains,mass disaster, number of osteons, sternal rib and regression formula.